ANALYSING WORD FORMATION PROCESSES OF THE LATEST UPDATED WORDS IN SEPTEMBER 2023 IN THE OXFORD ADVANCED LEARNER’S ONLINE DICTIONARY - Fatahillah, Muhammad Erfan; Eliwarti, Eliwarti; Syarfi, Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research is about the analysis of word formation processes of the latestupdated words in September 2023 in the Oxford Advanced Learner’s Online Dictionary(OALD). The objective of this research is to identify the types of word formation processes of the latest updated words in September 2023 in the OALD and to find out how the word formation processes occur in the latest updated words in September 2023 in the OALD. This research is a descriptive qualitative research. The source of the data is the latest updated words in September 2023 in the Oxford Advanced Learner’s Online Dictionary. The data were collected through document analysis. The instrument of this research is the researcher himself. The technique of data analysis used in this research is descriptive analysis. The researcher found 150 words containing word formation processes. There are nine types of word formation processes found in this research, namely borrowing, compounding, clipping, blending, backformation, conversion, acronym, derivation, and multiple processes. The most dominant type of word formation process found in this research is compounding. From 150 data, there are 100 datacontaining compounding.Key Words: word formation processes, latest updated words, online dictionary